Strategy of Management by Insurance Reserves of the Insurance Organizations - LUIBOV, Ulibina; SERIKOVA, Gulzira; OLGA, Okorokova; SEMBEKOV, Amir; VOROBYEVA, Svetlana; AFF, Josef (Journal of Advanced Research in Law and Economics, 2018)
In the article the author considers the mechanism of state regulation of formation and strategy of management of insurance reserves of insurance organizations of Russia, Kazakhstan and Belarus discussed the factors that determine the dynamics of the modern state and tendencies of development of insurance markets and their financial capacities, the structure of insurance reserves, the investment yield.